Multiwall carbon nanotube microcavity arrays - Ahmed, R.; Rifat, A.A.; Yetisen, A.K.; Dai, Q.; Yun, S.H.; Butt, H. (American Institute of Physics, 2016)
Periodic highly dense multi-wall carbon nanotube (MWCNT) arrays can act as photonic materials exhibiting band gaps in the visible regime and beyond terahertz range. MWCNT arrays in square arrangement for nanoscale lattice constants can be configured as a microcavity with predictable resonance frequencies. Here, computational analyses of compact square microcavities (≈0.8 × 0.8 μm2) in MWCNT arrays were demonstrated to obtain enhanced quality factors (≈170-180) and narrow-band resonance peaks. Cavity resonances were rationally designed and optimized (nanotube geometry and cavity size) with finite element method. Series (1 × 2 and 1 × 3) and parallel (2 × 1 and 3 × 1) combinations of microcavities were modeled and resonance modes were analyzed. Higher order MWCNT microcavities showed enhanced resonance modes, which were red shifted with increasing Q-factors. Parallel microcavity geometries were also optimized to obtain narrow-band tunable filtering in low-loss communication windows (810, 1336, and 1558 nm). Compact series and parallel MWCNT microcavity arrays may have applications in optical filters and miniaturized optical communication devices.